2017
DOI: 10.1080/19942060.2017.1292409
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of dynamic characterics for combined valves in multiphase pump

Abstract: This research presents theoretical analysis and numerical simulation of combined valves' dynamic characteristics in reciprocating oil-gas multiphase pump. Based on the mathematical model describing valves' motion, a geometric model of pump cavity and combined valves is put forward for numerical simulation in multiphase pump. The simulation is conducted by computational fluid dynamics (CFD) method with its dynamic grid technique. The motion process of suction valve and discharge valve are obtained on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…As a common power source, RPP uses the reciprocating movement of the plunger to periodically change the volume of the working chamber to transport fluid; now, it has become an indispensable part in many fields, such as automobiles and construction machinery [18,19]. The conventional RPP mostly uses one-way valves or solenoid valves for flow distribution [20][21][22]. The one-way valve has hysteresis when opening and closing; especially at high speed, the hysteresis of the one-way valve is more serious, which leads to lower VE of the pump.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a common power source, RPP uses the reciprocating movement of the plunger to periodically change the volume of the working chamber to transport fluid; now, it has become an indispensable part in many fields, such as automobiles and construction machinery [18,19]. The conventional RPP mostly uses one-way valves or solenoid valves for flow distribution [20][21][22]. The one-way valve has hysteresis when opening and closing; especially at high speed, the hysteresis of the one-way valve is more serious, which leads to lower VE of the pump.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering Boussinesq approximation along with aforesaid assumptions, the governing equations for the physical problem can be written as follows [3,4,11,12,14,16,17,32] :…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Akbarian et al [31] performed a numerical simulation of using natural gas in a dual-fueled constant-speed diesel engine and obtained results indicated that under different loads and pilot to gaseous fuel (PGF) ratios, the emissions of nitrous oxides and particle materials in the dual mode were lower than diesel engine. Ma et al [32] developed a mathematical model describing gas-liquid valves' motion and dynamical simulation of combined valves to analyze its working mechanism in reciprocating multiphase pump and provide theoretical foundation for the design of new type of multiphase pump. Das et al [33] developed a model to study mixed convection problem under the influence of uniform transverse magnetic force and observed that nanofluid velocity inside the channel enhanced by the imposed magnetic force.…”
Section: Introductionmentioning
confidence: 99%
“…The study provides a theoretical basis for the design of high-efficiency multiphase pump and valve. 16,17 Van et al proposed a novel fluid structure interaction (FSI) model for a piston diaphragm pump by immersed boundary methods. They used a combination of two different types of immersed boundary methods, a feedback forcing approach for interaction with the flexible structure, and a direct forcing approach for the interaction with the rigid structure.…”
Section: Introductionmentioning
confidence: 99%